Biomimetic gastric tract simulator : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Manawatu, New Zealand - Olson, Gerald (Massey University, 2023)
Mimicry of the biomechanical functioning of the human gastric tract can play a significant role in study of the behaviour of foods and food structures as they are broken down and digested in the human body. The gastric tract wall produces peristaltic waves and other deformation patterns providing movement, accommodation, mixing and evacuation of foods in the stomach and connected gastric tract organs. This thesis presents an advanced biomimetic dynamic in vitro model of the human gastric tract that simulates anatomic geometry and demonstrates the mixing and movement of gastric tract contents. Materials, methods, and techniques suitable for mimicking the gastric tract wall were investigated and artificial membrane layers, artificial muscles, muscle activation and control mechanisms, and feedback sensors were developed and integrated into a dynamic physical model of the gastric tract. A composite material of silicone rubber reinforced with a nylon elastic fabric provides a thin, watertight, and highly elastic artificial membrane that forms the shell of the tract. Artificial muscles made from loops of coiled nylon monofilament line, attached to the artificial membrane, are contracted, and expanded through the pulling and releasing of flexible tendons or cables. Contraction and expansion of the artificial muscles is carried out using winding mechanisms and motors, while feedback and control systems track and maintain the desired mechanical activity of the tract. Mimicry of the muscle and membrane layers of the gastric tract wall is a novel approach to simulating gastric tract biomechanics, resulting in a soft, highly flexible, and dynamic physical in vitro modelling of the geometrical, anatomic, and biomechanical functioning of the human gastric tract.
Figure 19 is reproduced with permission.
Keywords: Alimentary canal; Models; Biomimicry; 400303 Biomechanical engineering